A roadmap to reduce the risk of overexploiting EU marine living resources in a changing ocean - Bastardie, François; Salvany, Lara; Cooper, Anne M.; Carvalho, Natacha (Frontiers in Marine Science, 2024)
We provide a balanced overview of how risk assessment and management is being tackled in the European Union (EU) and beyond to address the challenges of overexploiting marine living resources in EU waters. We aim to guide EU fisheries and aquaculture policymakers towards key actions to foster the transition to responsible, sustainable, clean energy, and resilient fisheries and aquaculture sectors, aligning with EU environmental objectives under the European Green Deal and the Common Fisheries Policy. Despite progress in reducing fishing pressure on some stocks in recent years, most of the stated (single-stock) sustainability objectives still need to be met. The risk of overexploiting marine resources remains high, especially when combined with other pressures such as pollution and climate change. Risk is defined as the probability of an adverse event arising from natural or human activities and excessive pressures. Scientists have documented these pressures, proposing regional risk assessments to support adequate risk-based management of human activities impacting marine and coastal regions. As a next step, we recall actionable short- to long-term recommendations to reduce the risks associated with exploiting these natural resources and ensure their sustainability and resilience. This includes actions the EU can take to improve and implement fisheries policy while prioritising less harmful alternatives among current fishing methods and considering the three pillars of sustainability i.e. environmental, economic and social. Such actions include capturing in scientific advice the strong, causal links between pressures induced by human activities, natural disturbances and ecosystem states; such understanding can be used in an uncertain and changing environment, with ocean productivity possibly trending towards new levels. Finally, we restate that conserving by reducing pressures and restoring the integrity of marine ecosystems is crucial for minimising the risk of overexploitation and ensuring future fishing and farming opportunities. This is the aim of an Ecosystem Approach to fisheries and aquaculture – it should safeguard the long-term economic and social capital already invested by the public and private sectors in exploiting marine living resources to continue delivering healthy, low-carbon, low-impact seafood to EU citizens and beyond.